2022
DOI: 10.18092/ulikidince.938688
|View full text |Cite
|
Sign up to set email alerts
|

Kri̇pto Para Pi̇yasalarinda Nedenselli̇k Ve Eşbütünleşme

Abstract: This paper investigates the causality and cointegration relationships between seven major cryptocurrencies, namely Bitcoin (BTC), Binance Coin (BNB), Cardano (ADA), Dogecoin (DOGE), Ethereum (ETH), Polkadot (DOT) and Ripple (XRP), using Johansen Cointegration and Granger Causality tests over the period from August 21, 2020 to April 19, 2021. Results indicate that there exists cointegration among cryptocurrencies in the long run. Findings also show that there is a bi-directional causal relationship between BNB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Cryptocoins are known for their volatility and interdependence. Granger causality is a known tool to study the interdependence of cryptocoins, for instance [KCP21] found a strong relationship between Bitcoin (BTN) and Ethereum (ETH) and [Yav22] points out complex interdependence between the main cryptocoins.…”
Section: Real Datasetmentioning
confidence: 99%
“…Cryptocoins are known for their volatility and interdependence. Granger causality is a known tool to study the interdependence of cryptocoins, for instance [KCP21] found a strong relationship between Bitcoin (BTN) and Ethereum (ETH) and [Yav22] points out complex interdependence between the main cryptocoins.…”
Section: Real Datasetmentioning
confidence: 99%
“…The results of Viswanath-Natraj & Lyons [31] do not show systematic evidence that the price of cryptocurrencies, such as Bitcoin, influences Tether. According to Gul [32], Tether was not included in his study because Tether is a stablecoin whose price is indexed to the US dollar and exhibits different return and volatility characteristics than other cryptocurrencies.…”
Section: B Bitcoin Price Volatility Affects Tether Price Movementsmentioning
confidence: 99%